Management of Poverty Feminization Program of Women Head of Household in East Kalimantan Province - Widyatmike Gede Mulawarman; Suryaningsi Suryaningsi; Henny Pagoray; Endang Dwi Sulistyowati; Alfian Rokhmansyah (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
Background The phenomenon of women working outside the home is no longer a foreign of conversation. Objective The purpose of this research is to describe the struggle of the female head of the house to survive to support the family. Methods This research uses a qualitative approach with a case study method. The research data is in the form of observations and interviews with 10 female heads of households who live in Samarinda City. Results Based on the results of observations and interviews, economically the poverty that occurs in female heads of household is due to: a) There is no good management from the government related to human resources so that assistance does not run optimally. b) Lack of ownership of land assets, decent housing for families, salary erratic activities that interfere with the activities of women heads of households, c) The lack of working capital that is currently being carried out, economic activities are carried out with minimal capital, d) There are no business facilities, women heads of households only rely on capital assistance, and e) Economic efforts for survival has not been maximized and there is no good management from the government. Conclusion Female heads of households need not only capital intake but also assistance to improve life skills to create family resilience. Implication practice This research can be used as statistical data for female heads of households in formulating programs activities to alleviate poverty for female heads of households.